Structure of metal melt - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия, 2020)
Modern conventional notions of metallic melt structure are associated with clusters that have no interfacial boundaries. The maximum time of formation and life of the cluster is 10–7s. Clusters are formed statistically, randomly. According to probability theory, even an elementary cubic crystal cannot be formed in a time of 10–7c. The probability of forming a cluster with 100 atoms is zero. It should be considered that the metallic melt is mainly composed of nanocrystals.